Metode Selimut Insulasi Panas untuk Pencegahan Penurunan Suhu Tubuh Bayi Tikus Putih - Diah Eka Nugraheni; Elvi Destariyani; Sri Sumiati (Politeknik Kesehatan Tanjung Karang, 2019)
The temperature decrease is caused by heat loss by conduction, convection, evaporation, and radiation. Various methods for preventing heat loss in newborns include the use of plastic bags. Nugraheni's research in 2016, the use of plastic wrap in newborns can still result in body heat loss because polyethylene plastic is not heated insulation. Aluminum foil is one of the ingredients that insulates heat insulation. The use of aluminum foil is widely used in various fields, for example as a food wrap to keep it warm and an emergency blanket for mountain climbers. This study aims to determine the comparison of the use of blanket heat insulation and plastic wrap in preventing the decrease in body temperature of babies of white rats. The type of research used was quasi-experimental (Quasi-Experiment) with the design of